Associations of work-related extended availability with overweight and obesity among Chinese workers - Huiying Wang; Xin Li (Frontiers in Public Health, 2026)
Objective Work-related extended availability (WREA) has become an increasingly salient feature of the contemporary labor market and may be associated with workers' health outcomes. Nevertheless, the associations of WREA with overweight and obesity remain insufficiently explored. This study aimed to examine the associations of WREA with overweight and obesity among Chinese workers. Methods Using data from the 2020 and 2022 waves of the China Family Panel Studies, we constructed an analytical sample of 16,969 observations and employed ordered logistic regression models (ologit) to examine the associations of WREA with overweight and obesity. The models adjusted for a comprehensive set of covariates, including demographic characteristics, health status and behaviors, job characteristics, and socioeconomic factors. A series of sensitivity analyses was performed to assess the consistency of the main findings. We also conducted exploratory analyses to examine heterogeneity across demographic subgroups, potential effect modification by work- and family-related factors, variation across study-defined WREA categories, and the longitudinal association of WREA with subsequent overweight and obesity. Results The reported prevalence rates of overweight and obesity were 31.95 and 9.92%, respectively, and 53.29% of workers were exposed to WREA. Overall, WREA was positively associated with the prevalence of overweight (average marginal effect = 0.019, 95% CI = 0.011 to 0.028) and obesity (average marginal effect = 0.012, 95% CI = 0.007 to 0.019). These associations remained broadly consistent across a series of sensitivity analyses. In exploratory heterogeneity analyses, the estimated associations tended to be more pronounced among men, individuals with medium educational attainment, and those aged 30–50 years. Additionally, the estimated associations also appeared to vary by employment status and the financially support for parents. Exploratory category-specific analyses suggested variation across the study-defined WREA categories, with estimates tending to be larger for contract-based and digitally enabled WREA. However, an exploratory longitudinal analysis did not provide sufficient evidence of associations between WREA and subsequent overweight or obesity. Conclusions WREA was positively associated with the prevalence of overweight and obesity. As WREA becomes an increasingly salient feature in modern workplaces, its potential occupational health implications warrant further investigation and attention.